Resilient Computing Curriculum Draft -- ReSIST NoE Deliverable D16 - Simoncini, L. (2009)
This Deliverable presents the first version of ReSIST's Curriculum in Resilient Computing, limited to the description of the syllabi for the first year (Semesters 1 and 2) and indicates the line and title for the curriculum in the second year (semesters 3 and 4) and propose it to the general discussion for improvements. The curriculum will be updated and completed in successive versions that will take advantage of a large open discussion inside and outside ReSIST